Comparison of the Rotational Stability of Different Toric Intraocular Lens Implants - Kate C. Torio, MD; Robert Edward T. Ang, MD; Gladness Henna A. Martinez, MD; Jocelyn Therese M. Remo, MD (Philippine Journal of Ophthalmology)
Objective: To compare the rotational stability and cylinder reduction of different toric intraocular lenses (IOLs).